REGULASI DIRI DAN KONTROL DIRI TERHADAP FEAR OF MISSING OUT (FOMO) PADA REMAJA - Nafisah, Putri Sayyidah; Pramintari, Ratna Duhita; Nurhidayah, Siti (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2024)
Fear Of Missing Out (FOMO) is a widespread feeling of fear, anxiety and depression that a person experiences when someone is not aware of what is happening in cyberspace or in the real world, making people get to know each other to stay connected on social media so that they don't miss what other people are experiencing. One thing that influences fomo is self regulation and self-control. This research is quantitative research with a research design using correlation research and multiple linear regression. The research subjects were 169 teenage respondents in the city of Bekasi. with simple cluster sampling technique. Data collection in this research used psychological scales and interviews. The instrument used is a psychological scale consisting of a fear of missing out (FOMO) scale, a Self-Regulation scale and a Self-Control scale. The instrument reliability test using the Cronbach's Alpha formula produced a ralpha value = 0.790 for the fear of missing out (FOMO) scale, a ralpha value = 0.941 for the self-regulation scale and a ralpha value = 0.902 for the self-control scale. Data analysis in this study used the Spearman rank correlation technique and multiple linear regression tests to test the hypothesis. The results of research between the social variables of self-regulation and self-control on fear of missing out (FOMO), show an F value of 8.075 with the results of the significance test showing a value of 0.000 (Sig, ≤ 0.05). Self regulation and self-control together influence fear of missing out (FOMO) by 9.0%, while 91% is influenced by other variables not examined in this study.